2019
DOI: 10.17221/67/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of mastitis and its effect on the milk malondialdehyde concentrations and blood enzymatic antioxidants in dairy cows

Abstract: Early identification of mastitis is a serious challenge for dairy farmers and veterinarians in ensuring the health of an animal and the hygienic quality of the produced milk. The purpose of this study was to detect the occurrence and aetiology of mastitis in a dairy herd of 15 milked cows localised in a farm in west Slovakia. During the complex investigation, 606 quarter milk samples were examined (6 quarters were discarded) and classified based on the clinical status, the presence of abnormal udder secretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…As has been stated earlier (Hosseinzadeh and Saei 2014;Vakkamaki et al 2017), the isolation of a CoNS species in a pure culture was regarded as remarkable, and they were ascribed as the causative agents of the subclinical mastitis cases examined herein. The results presented in the current study were in full agreement with the results of Alekish (2015), Srednik et al (2017) and Zigo et al (2019) who reported S. chromogenes as the most prevalent species, whereas, there were slight differences with the findings of Cervinkova et al (2013), El-Jakee et al (2013 and Hosseinzadeh and Saei (2014) who described other species as the most widespread. Such differences were not considered as unexpected because of the possible differences of the CoNS strains circulating among the cattle populations in a given geographic location.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As has been stated earlier (Hosseinzadeh and Saei 2014;Vakkamaki et al 2017), the isolation of a CoNS species in a pure culture was regarded as remarkable, and they were ascribed as the causative agents of the subclinical mastitis cases examined herein. The results presented in the current study were in full agreement with the results of Alekish (2015), Srednik et al (2017) and Zigo et al (2019) who reported S. chromogenes as the most prevalent species, whereas, there were slight differences with the findings of Cervinkova et al (2013), El-Jakee et al (2013 and Hosseinzadeh and Saei (2014) who described other species as the most widespread. Such differences were not considered as unexpected because of the possible differences of the CoNS strains circulating among the cattle populations in a given geographic location.…”
Section: Discussionsupporting
confidence: 92%
“…Various CoNS species including S. sciuri (Cervinkova et al 2013), S. chromogenes, S. epidermidis andS. haemolyticus (Alekish 2015;Srednik et al 2017;Zigo et al 2019) have been described as the most prevalent isolates obtained from either the clinical or subclinical bovine mastitis. After detecting S. chromogenes and S. epidermidis as the most frequently isolated species with frequencies of 19.4% and 16.7%, respectively, Alekish (2015) concluded that the subclinical mastitis caused by CoNS should be considered as a significant heath issue for dairy heifers in Jordan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in oxidative stress in bovines with mastitis was observed by increasing the consumption of dietary antioxidants ( Sharma, Verma, Rahal, Kumar & Nigam, 2016 ). The early diagnosis of subclinical mastitis through the use of the relation between MDA and enzymatic antioxidants (SOD, GPx) has been reported ( Abdel-Hamied & Mahmoud, 2020 ; Mahapatra, Panigrahi, Patra, Rout & Ganguly, 2018 ; Yang et al., 2011 ; Zigo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of the ROS correlating with a chemical and physical changes in the milk and can lead to oxidative stress. Increase of oxidative stress in dairy cows because of high milk production can result in excess accumulation of ROS, which can induce lipid peroxidation and reduction of antioxidative activity [2].…”
Section: Introductionmentioning
confidence: 99%